Revisiting Mudharabah Investment Account and Proposal for Improvement – Case of Indonesia - Wibisono, Afrid; Siregar, Hermanto; Ismal, Rifki; Ratnawati, Nirdukita; Ismail, Ahmad Faizal (AL-MUZARA'AH, 2024)
The rapid growth of Islamic banks is accompanied by various innovations in Islamic financial transactions which generally seem to follow the product diversity and risk profile of conventional banks. This innovation is also carried out in the application of mudharabah particularly in the Profit-Sharing Investment Account (PSIA). Mudharabah, whose original form is equity, has been adapted by Islamic banks by treating it just like a normal deposit whith the exception that the profit is calcualted based on a ratio, resulting difficulties to distinguish it from conventional bank deposits which are debt in nature. This research aims to evaluate the implementation of mudharabah in PSIA in Indonesia, by conducting field survey and interviews with parties whom responsible for managing it and comparing it with Sharia Standard issued by Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and fatwas of National Sharia Council of Indonesian Ulama Council (DSN-MUI). The research revealed that although PSIA return is calculated using profit distribution ratio (as mudharabah core feature), it lacks other main features of mudharabah, be it in its nature or profit or loss determination method. To rectify this deviation, this research proposes an operational model of mudharabah termed “the Quasi Equity Model", which meets the main features of mudharabah as envisaged by AAOIFI and DSN-MUI. This study contributes to the field of Islamic finance by not only identifying existing discrepancies but also proposing a practical model for addressing them, thus aligning it back to sharia principles within Islamic banking practices.